2018
DOI: 10.1101/501924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response to a Synthetic Pheromone Source by OX4319L, a Self-Limiting Diamondback Moth (Lepidoptera: Plutellidae) Strain, and Field Dispersal Characteristics of Its Progenitor Strain

Abstract: The Diamondback Moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is a global pest that infests vegetable and field crops within the Brassica family. A genetically engineered strain of P. xylostella, OX4319L, carrying a self-limiting gene, has shown potential for managing P. xylostella populations, using sustained releases of OX4319L male moths. In order for such a strain to provide control, the transgenic individuals must exhibit attraction to female P. xylostella sex pheromone and adequate dispersal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The moths were placed at the bottom and the behaviour was found similar among all four strains of diamondback moth on the basis of three check points whether they take flight, fly upwind direction or reach close to lure. This result confirmed that, transgenic and wild diamondback moth strains showed almost similar response towards female sex pheromone (Bolton et al, 2019).…”
Section: B Diamond Back Moth P Xylostellasupporting
confidence: 86%
“…The moths were placed at the bottom and the behaviour was found similar among all four strains of diamondback moth on the basis of three check points whether they take flight, fly upwind direction or reach close to lure. This result confirmed that, transgenic and wild diamondback moth strains showed almost similar response towards female sex pheromone (Bolton et al, 2019).…”
Section: B Diamond Back Moth P Xylostellasupporting
confidence: 86%
“…albopictus, Anopheles albimanus and An. stephensi (Fu et al, 2010;Wise de Valdez et al, 2011;Labb e et al, 2012;Slade and Morrison, 2014) and agricultural pests such as the diamondback moth (Plutella xylostella; strain OX4319L; Harvey-Samuel et al, 2015;Bolton et al, 2019), fall armyworm (Spodoptera frugiperda; strain OX4319; Jin et al, 2013), pink bollworm (Pectinophora gossypiella; strains OX3402C, OX4135 and OX4319; Simmons et al, 2011;Morrison et al, 2012;Jin et al, 2013), Mediterranean fruit fly (C. capitata; strain OX3864A; Leftwich et al, 2014;Asadi et al, 2019) and olive fly (Bactrocera oleae; strain OX3097D; Ant et al, 2012;Turner et al, 2018). These strains also express the fluorescent protein marker, DsRed, to permit the effective monitoring of the presence of such strains in the field.…”
Section: Release Of Genetically Modified Insects With a Dominant (Female) Lethal Transgenementioning
confidence: 99%
“…This self-limiting technology is also being developed to control arthropod pest species such as the fall army worm (Spodotera frugiperda), diamondback moth (Plutella xylostella), olive fly (Bactrocera olea), Mediterranean fruit fly (Ceratitis capitata) and the spotted wing drosophila (Drosophila suzukii) (www.oxitec.com). Small scale field trials took place in 2017 in Geneva (NY, USA) with the OX4319L diamondback moth to test dispersal, survival and efficacy in suppression of the local diamondback moth population on cotton (Bolton et al, 2019). Previous glasshouse experiments have demonstrated the effectiveness of this approach (Harvey-Samuel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%